Excitation of Gould–Trivelpiece mode by streaming particles in dusty plasma. (2nd April 2019) - Kaur, Daljeet; Sharma, Suresh C.; Pandey, R.S.; Gupta, Ruby
Abstract: In this paper, we study the excitation of Gould–Trivelpiece (TG) waves by streaming ions in dusty plasma and derive the dispersion relation of the excited waves using first-order perturbation theory. The motion of charged particles is controlled by electromagnetic fields in plasma. The energy transfer processes which occur in this collisionless plasma are believed to be based on wave–particle interactions. We have found that the TG waves may be generated in a streaming ion plasma via Cerenkov interaction, and the ions may be accelerated by TG waves via cyclotron interaction, which enable energy and momentum transfer. The variation in the growth rate of TG wave with dust grain size and relative density of negatively charged dust grains is also studied. The dust can cause an unstable TG mode to be stable in Doppler resonance, and can induce an instability in Cerenkov interaction.